SIX SIGMA, BALANCE SCORECARD, DAN KAITANNYA DENGAN AUDIT MANAJEMEN - NIVIARI, NANIEK (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 3 No 1 (2008), 2008)
Performance measurement is important factor for enterprises. Performance measurement can be used to evaluate enterprises effectiveness and to arrange reward sysem. There are many tools for performance measurement such as Six Sigma and Balance Scorecard. This paper discuss how Six Sigma and Balance Scorecard are used in performance measurement and relation between management audit and Six Sigma and Balance Scorecard. Six Sigma and Balance Scorecard are used in performance measurement by DMAIC methode (define, measure, analyze, improvement, control). Management auditor can use Six Sigma to evaluate management performance. BSC can be used by auditor management to balance financial performance measurement as lag factor and other nonfinancial performance measurement as lead factor, such as customer, internal bussines process, and learning & growth perspektif (BSCFirst Generation). But in BSC-third Generation, the relationship between management audit with BSC is if we want to design Enterprise BSC, we must do audit management first.
Keywords: performance measurement, Six Sigma, Balance Scorecard, audit management